2021
DOI: 10.1186/s13063-020-04969-w
|View full text |Cite
|
Sign up to set email alerts
|

The reality of informed consent: empirical studies on patient comprehension—systematic review

Abstract: Background Informed consent is a basic concept of contemporary, autonomy-based medical practice and facilitates a shared decision-making model for relations between physicians and patients. Thus, the extent to which patients can comprehend the consent they grant is essential to the ethical viability of medicine as it is pursued today. However, research on patients’ comprehension of an informed consent’s basic components shows that their level of understanding is limited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 22 publications
0
80
0
3
Order By: Relevance
“…This may lead to research participants having difficulty understanding the information contained in PIL/ICFs prior to providing their consent to take part. Concerningly, a recent systematic review indicated that research participants often have a poor understanding of some of the key concepts needed to ensure valid informed consent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may lead to research participants having difficulty understanding the information contained in PIL/ICFs prior to providing their consent to take part. Concerningly, a recent systematic review indicated that research participants often have a poor understanding of some of the key concepts needed to ensure valid informed consent [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The website and the enhanced PIL/ICF contain the same informational content, but the website also includes some animations which support the written content. The animations on the website were developed in conjunction with the Educational Technology team at the School of Medicine, University College Dublin, and focus mainly on two aspects which have been demonstrated to be poorly understood by research participants: randomisation and risks/side effects [ 5 ]. The enhanced PIL/ICF is included as a supplementary file (see Additional file 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, there is an increasing body of evidence, causing significant concern, over the true level of understanding of research participants. Recent systematic reviews have suggested that research study participants often have a poor understanding of vital concepts which are important in ensuring valid informed consent [ 4 , 5 ]. This includes concepts surrounding randomisation and the risks/side effects of participating, which participants find particularly difficult [ 6 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…43 A systematic review concluded that, in general, patients demonstrated lower levels of comprehension regarding aspects of consent, whilst crucial information, including benefit-risk, voluntariness and the relation between clinical trials and standard therapy are poorly understood by many participants; severely compromising existing practices intended to provide a sound ethical rationale for research with human subjects. 44 Therapeutic misconceptions. Research participants, often with pre-existing conditions, may be susceptible to overestimating the benefits/underestimating the risks of early phase trials and may misunderstand the distinctions between research and individualised care, -a concern referred to as the 'therapeutic misconception'.…”
Section: What Constitutes 'Adequate' Informed Consent?mentioning
confidence: 99%